Competitiveness and Determinants of Indonesian Frozen Shrimp Exports to Non-Traditional Markets - Rindayati, Wiwiek; Akbar, Raihan (School of Business, Bogor Agricultural University (SB-IPB), 2022)
Shrimp is an Indonesian fishery commodity with a high selling value in domestic and international markets. Frozen shrimp, as a type of shrimp exported from fishery products, has enormous potential to be developed as one of the mainstay commodities in the fisheries sector. However, Indonesia's frozen shrimp exports in the last five years have fluctuated and are still unable to compete with competing countries in exporting to main destination countries. Expanding the export market by looking at non-traditional markets as new destination markets to increase its exports again is necessary. This study analyses the competitiveness and determinants of Indonesian frozen shrimp exports to non-traditional markets. The research methods used are Revealed Comparative Advantage (RCA), Export Product Dynamic (EPD), X-Model to analyze the competitiveness and panel data regression to analyze determinants of Indonesian frozen shrimp exports to non-traditional markets. The results showed that Indonesian frozen shrimp are competitive in several non-traditional market destination countries. The estimation results in panel data regression show that the variables of real GDP per capita of the destination country, economic distance, export prices, actual exchange rates, population growth, and Logistic Performance Index (LPI) Indonesian and country of destination have a significant influence on Indonesia's frozen shrimp exports to non-markets traditional. Keywords: EPD, frozen shrimp, non-traditional market, panel data regresion, RCA, X-Model